Male-to-Female (MtoF) gender affirming surgery: Modified surgical approach for the glans reconfiguration in the neoclitoris (M-shape neoclitorolabioplasty) - Andrea Cocci; Francesco Rosi; Davide Frediani; Michele Rizzo; Gianmartin Cito; Carlo Trombetta; Francesca Vedovo; Simone Grisanti Caroassai; Augusto Delle Rose; Valeria Matteucci; Piero Buccianti; Cristina Ceccarelli; et al. (Archivio Italiano di Urologia e Andrologia, 2019)
Purpose: The aim of this article is to describe our modified surgical technique for the reconfiguration of the glans in the clitoris and the labia minora, known as the “M-shape neoclitorolabioplasty”. Methods: The glans with all its neurovascular bundle is isolated from the corpora cavernosa, incised in Y-shape mode and spread in order to obtain an M-shape glandular flap. The “belly” of the M-shape glans will constitute the triangular neoclitoris meanwhile the lateral flaps will constitute the labia minora. The inferior apex of the neoclitoris is fixed to the superior apex of the previously spatulated urethra. The two glans flaps are incised transversally to increase their length and sutured to the sides of the spatulated urethra forming the labia minora. Our technique permits to create an aesthetically pleasing neovagina preserving all the glandular erogenous sensitivity. Results: 94 patients have been treated with our modified technique of male-to-female (MtoF) gender affirming surgery. At median follow-up of 27.57 months, 81 (86.1%) patients reported vaginal intercourse and 78 (82.9%) patients referred presence of erogenous sensitivity during dilatations, intercourse or masturbations. All the glandular tissue is preserved and reconfigured forming the neoclitoris and the labia minora. The M-shape reconfiguration permit to create an aesthetically pleasant neoclitoris. Conclusions: This technique could be applied safely and easily to patients undergoing gender affirming surgery, allowing the creation of a neovagina with the best possible erogenous sensitivity without losing aesthetical results.